Language and Culture Appropriate Approaches Needed to Improve Health Education to Reduce Disparities among Korean American Immigrants Living in Los Angeles - Kim, Jayoung; Shahid, Muhammad; Yeon, Austin; Cho, Eunho; Bae, Jooeun; Park, Rebekah J. (International Journal of Innovative Research in Medical Science, 2018)
This study aimed to determine the disparities associated with health awareness and access to health education among Korean American residents living in the Los Angeles area. In particular, this research focused on gathering data on how Korean American immigrants perceive health information and what major barriers prevent them from gaining access to healthcare. In total, 421 Korean Americans living in Los Angeles participated in this study. The constructed 13-item questionnaires were provided in a pen and paper or online version in Korean or English. The quantitatively evaluated data revealed the status of exercise, smoking, access to healthcare, health interest, alcoholic consumption et al. in female and male subjects. Our study found that older age groups chose the paper survey option rather than the online version. They also preferred the Korean-translated survey over the English one. These findings suggest that careful consideration on language and format is required when assessing healthcare access in older generation Korean Americans. The major health concern of the paper survey group was also cancer prevention.